1994
DOI: 10.1111/j.1699-0463.1994.tb04866.x
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of Danish isolates of Salmonella enterica serovar Enteritidis by phage typing and plasmid profiling: 1980–1990

Abstract: Plasmid profiling, phage typing and antimicrobial resistance typing have been carried out on 736 isolates of Salmonella enterica serovar Enteritidis collected in Denmark during the period 1980 to 1990. Strains originated from cases of human salmonellosis, broiler poultry flocks, layer poultry flocks, quarantined imported poultry, environmental samples from hatchery units, and from bovines. Phage type (PT) 1 was found to be the most common type among isolates of poultry origin (57.6%) followed by PT4 (28.8%). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Amongst S. Enteritidis isolates, the prevalence of multi-resistance was considerably low, 1.4%, a Wnding in agreement with report of Yang et al (2002) but considerably lower than that found by Dias de Oliveira, Siqueira Flores, Dos Santos, and Brandelli (2005). Similarly, the prevalence of resistance, as determined by resistance to one or more antimicrobial agents, although higher than reported for isolates from table eggs by Brown et al (1994) is signiWcantly lower than found in Brazil (Simango & Mbewe, 2000). It has been reported that inappropriate use of antimicrobial agents in livestock may result in the development of resistance amongst bacteria in these animals or their products (Washington, 1979;Waltner-Toews & McEwen, 1994).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Amongst S. Enteritidis isolates, the prevalence of multi-resistance was considerably low, 1.4%, a Wnding in agreement with report of Yang et al (2002) but considerably lower than that found by Dias de Oliveira, Siqueira Flores, Dos Santos, and Brandelli (2005). Similarly, the prevalence of resistance, as determined by resistance to one or more antimicrobial agents, although higher than reported for isolates from table eggs by Brown et al (1994) is signiWcantly lower than found in Brazil (Simango & Mbewe, 2000). It has been reported that inappropriate use of antimicrobial agents in livestock may result in the development of resistance amongst bacteria in these animals or their products (Washington, 1979;Waltner-Toews & McEwen, 1994).…”
Section: Discussionsupporting
confidence: 83%
“…A prevalence of 22.9% for resistance to antimicrobial agents detected amongst Salmonella isolates from eggs is considerably lower than the prevalence of 50% reported for Salmonella isolates recovered from livestock in Trinidad (Adesiyun, Kaminjolo, Loregnard, & Kitson-Piggott, 1993) and elsewhere (Brown, Baggesen, Hansen, Hansen, & Bisgaard, 1994;Hang'ombe et al, 1999;Poppe, 1994;Neu, Cherubin, Longo, Flouton, & Winter, 1975;Wray, Beedell, & McLaren, 1991). Amongst S. Enteritidis isolates, the prevalence of multi-resistance was considerably low, 1.4%, a Wnding in agreement with report of Yang et al (2002) but considerably lower than that found by Dias de Oliveira, Siqueira Flores, Dos Santos, and Brandelli (2005).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Serotyping or other typing methods are necessary epidemiological tools in studies of zoonotic bacteria. For example, combined serotyping and phage‐typing of salmonella isolates from humans, layer hens, broiler chickens, swine and cattle were used for assessing the significance of different production animals as a source of human infection [6, 7]. For campylobacters, comparison of types isolated from humans and potential sources of human infection has not been done over long time periods and to the same extent.…”
Section: Introductionmentioning
confidence: 99%
“…Phage typing has been found to be useful for the tracking of spatial and temporal distributions of S. Enteritidis. For example, phage type 8 (PT8), PT13a, and PT13 are taken to be most common in North America (5,6), while PT4 has been the dominant phage type in most countries of Western Europe (7)(8)(9). Additionally, PT14b represents a phage type that recently emerged in southern European countries in 2001 (10).…”
mentioning
confidence: 99%